Post-Occupancy Performance Evaluation of the relocated housing in Labuha Village, South Halmahera Regency - Ali, Muhammad; Marsoyo, Agam (PT Mattawang Mediatama Solution, 2025)
This study was conducted to evaluate the performance of relocation housing as a whole through the Post-Occupancy Evaluation (POE) approach. The evaluation focuses on three main aspects: technical, functional, and behavioral. These three aspects were chosen to see the extent to which this relocation housing is able to meet the physical, functional, and social needs of residents according to the principles of decent and sustainable housing. This study uses a quantitative approach reinforced with qualitative data through observation, questionnaires, and in-depth interviews. The analysis was carried out by classifying the evaluation scores into good, adequate, and bad categories for each observed sub-variable. The triangulation method was applied to ensure the validity of the data, by comparing the results of technical observations in the field, residents' perceptions through questionnaires, and deepening issues through interviews. This approach allows for a holistic assessment of residential performance from various perspectives. The results showed that the technical aspect had the weakest performance, with many sub-variables being categorized as